Preexodic Expression of Juozas Tarulis - Racevičiūtė, Eglė (Respectus Philologicus, 2001)
This article is a literary experiment. It doesn't merely seek mystical, anarchic, etc. emotional expressions, doesn't "go after" the mood of catastrophe, drastic contrasts, shocking ideas, but pays attention to the emotionality of the text, its visual structures and seeks harmony. This work may be rewarding to those, who aren't uptight and aren't obligated to tradition, don't pay attention to A. Jakštas fears, as if such attitude were a deadly sin, as if Lithuanian expressionists could be discussed only in terms of German theory. Germans are convinced that various -isms lack cultural threshold or national consciousness or tradition or ... and have only "untamed works of art" - works, which have no reins to control a content or a form. The author thinks that Tarulis and his writing were unbridled and she has strong arguments to verify her "assumption".
Keywords: -